ANALISIS PENGARUH KINERJA PENGAWAS KAMAR TERHADAP KEPUASAN TAMU DI HOTEL PACIFIC PALACE BATAM - Silvia Pratama Aneke Putri; Andri Wibowo; Arina Luthfini Lubis (JURNAL MATA PARIWISATA, 2023)
Tourism is described as an economic activity that attracts people and encourages them to stay in certain places, either permanently or temporarily. Batam City, one of the main cities in the Riau Archipelago Province, has the potential to become a tourist attraction. Pacific Palace Hotel Batam is the most distinctive hotel in Batam City, with a ship-shaped building inspired by Greek mythology, the sea god Neptune, and a spectacular interior design. Guest happiness is also an indicator of the company's future success. Guests are happy when their expectations are met, and they are even happier when their expectations are exceeded. However, if the visitor is not satisfied it can hurt the business and make the customer unhappy. Monte Carlo Sig. Calculations (2-tailed) produce a value of 0.255 for the normality test using the one-sample Kolmograv-Smirnov Test calculation. This variable has a significant value greater than 0.05 which indicates that the data in this study are regularly distributed. The linearity test produces a significant value that deviates from the linearity of 0.891 when the significance value is greater than 0.05. It can be stated that there is a fairly large linear relationship between service quality and guest satisfaction measures. The Validity Test findings were collected based on the data obtained from the questionnaire results, and using the Pearson Product Moment correlation, it was claimed that all data was valid. According to the reliability test, the data is credible because the Cronbach alpha value is more than 0.60. A significant value of 0.000 0.05 was achieved using the simple linear regression test, indicating that the variable quality of room attendant service (X) had an influence on visitor satisfaction (Y). According to the determinant coefficient or R2 test findings, which is equivalent to 0.490 or 49%. It is possible to establish that service quality has a 49% impact on guest satisfaction.